Developing a resort wastewater treatment system using plasma technology - Tran, Ngoc Dam; Hoang , Dinh Hai; Le, Quang Hung; Hoang, Ha; Trinh, Thanh Son; Jörn Kasbohm,; Nguyen, Van Suc (Journal of Technical Education Science, 2018)
The resort wastewater has been not only strongly negative affected to tourist city specially rivers and beaches but also to human life in large area. It comes from original source such as hotel and restaurant which have a lot of organics, chemicals and bacteria. The disadvantages of the currently state are the using treatment systems with low treatment efficiency, costly and unstable due to using microbiological, biochemistries, combining physical chemistry method, or advanced oxidation process. In this study, a resort wastewater treatment system using plasma at low temperature and atmospheric pressure was designed and developed to solve the above disadvantages. An 480l/h treatment system was completed and assembled in the Sam Son resort, Thanh Hoa to test and evaluate the treatment efficiency. In order to prove the stability of the processing system, before and after treating, wastewater samples were collected and tested at various times. The results showed that treatment efficiency reached to 70-90% and satisfy QCVN 14: 2008/BTNMT in column A. The system is stable, low cost, safe, non-chemicals, automated and saving energy.